LEAP2 is associated with impulsivity and reward sensitivity depending on the nutritional status and decreases with protein intake in humans - Andreoli, Maria Florencia (2024)
Aim: Liver-expressed antimicrobial peptide 2 (LEAP2) dynamics in human plasma and its association with feeding behaviour remain poorly understood. Therefore, this study aims: (a) to investigate fasting LEAP2 in participants with normal weight or with overweight or mild obesity (OW/OB); (b) to study the association between fasting LEAP2 and anthropometric and metabolic traits, feeding behaviour, LEAP2 genetic variants and blood cell DNA methylation status; and (c) to ascertain postprandial changes in LEAP2 after high protein intake and the association with feeding behaviour and food intake. Methods: Anthropometric and behavioural measures, genotyping, methylation profiling, plasma glucose and LEAP2 concentrations were assessed in 327 females and males. A subgroup of 123 participants received an ad libitum high-protein meal, and postprandial LEAP2 concentration and behavioural measures were assessed. Results: LEAP2 concentration was higher in participants with OW/OB (p < 0.001) and in females (p < 0.001), and was associated with LEAP2 single nucleotide polymorphisms rs765760 (p = 0.012) and rs803223 (p = 0.019), but not with LEAP2 methylation status. LEAP2 concentration was directly related to glycaemia (p = 0.001) and fullness (p = 0.003) in participants with normal weight, whereas it was associated with body mass index (p = 0.018), waist circumference (p = 0.014) and motor impulsivity in participants with OW/OB (p = 0.005). A negative association with reward responsiveness was observed in participants with OW/OB (p = 0.023). LEAP2 concentration was inversely associated with food intake (p = 0.034) and decreased after a high-protein meal (p < 0.001), particularly in women (p = 0.002). Conclusion: Increased LEAP2 in participants with OW/OB is associated with behavioural characteristics of obesity. Our results show sexual dimorphism in LEAP2 concentration before and after food intake and highlight the role of LEAP2 in feeding regulation.